Identifikasi Tingkat Kekumuhan di Kelurahan Mandala Distrik Jayapura Utara Kota Jayapura - Soleman Patai; Deasy Widyastomo; Marulitua Manalu (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
This research discusses the identification of slum level in Mandala Sub-district, North Jayapura District, Jayapura City. The research employs a qualitative descriptive approach with primary data obtained from observations, interviews, and documentation. Mandala Sub-district faces issues of development inequality and high population density, including unsuitable living conditions in its residential areas. The identification results indicate that the slum level in Mandala Sub-district falls under the category of "Mild Slum (KR)" according to the Ministry of Public Works and Housing Regulation No. 2 of 2016. The recommended approach for handling slum areas is through redevelopment, which includes improving housing and the surrounding environment, enhancing the quality of neighborhood roads, providing better access to clean water, managing wastewater, waste disposal, and fire protection measures. This research is expected to provide an overview and recommendations for more effective and sustainable handling of slum areas, involving the collaboration of the government, private sector, and community.